Efikasi Diri Kreatif Memediasi Intelegensi terhadap Perilaku Kerja Inovatif pada UMKM di Kota Bengkulu - Praningrum; Anggri Puspita Sari; Ilsya Hayadi (Jurnal Manajemen dan Organisasi, 2022)
MSME in Indonesia is increasingly growing and developing, thereby increasing competition among them. For this reason, business people are required to have the creativity and innovative behavior, but in reality, not all of them pay attention to it. The research objective was to analyze innovative work behavior by mediating creative self-efficacy on MSME in Bengkulu City. The survey collected primary data using a questionnaire with a Likert scale distributed offline using the hand-delivered survey method. Sampling using a convenience sampling method and obtained a sample of 115 respondents. Based on the calculation of the convergent validity, discriminant validity, and reliability testing, the results obtained were not all indicators were declared valid and reliable, so not all indicators were used as measurements in this study. The data analysis method used is descriptive analysis and Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results showed that intelligence has a positive and significant effect on innovative work behavior. Intelligence has a positive and significant impact on creative self-efficacy. Creative self-efficacy positively and significantly affects innovative work behavior and full mediation of creative self-efficacy on intelligence on innovative work behavior. This study is essential to spur the innovative behavior of MSME actors. The research results can be used as a basis for the government to instill creative work behavior towards MSME actors.